Developing a Framework for Predicting Upper Extremity Muscle Activities, Postures, Velocities, and Accelerations During Computer Use: The Effect of Keyboard Use, Mouse Use, and Individual Factors on Physical Exposures. - Garza, Jennifer L. Bruno; Catalano, Paul J.; Katz, Jeffrey N.; Huysmans, Maaike A.; Dennerlein, Jack T. (Journal of Occupational & Environmental Hygiene, 2012)
Prediction models were developed based on keyboard and mouse use in combination with individual factors that could be used to predict median upper extremity muscle activities, postures, velocities, and accelerations experienced during computer use. In the laboratory, 25 participants performed five simulated computer trials with different amounts of keyboard and mouse use ranging from a highly keyboard-intensive trial to a highly mouse-intensive trial. During each trial, muscle activity and postures of the shoulder and wrist and velocities and accelerations of the wrists, along with percentage keyboard and mouse use, were measured. Four individual factors (hand length, shoulder width, age, and gender) were also measured on the day of data collection. Percentage keyboard and mouse use explained a large amount of the variability in wrist velocities and accelerations. Although hand length, shoulder width, and age were each significant predictors of at least one median muscle activity, posture, velocity, or acceleration exposure, these individual factors explained very little variability in addition to percentage keyboard and mouse use in any of the physical exposures investigated. The amounts of variability explained for models predicting median wrist velocities and accelerations ranged from 75 to 84% but were much lower for median muscle activities and postures (0-50%). RMS errors ranged between 8 to 13% of the range observed. While the predictions for wrist velocities and accelerations may be able to be used to improve exposure assessment for future epidemiologic studies, more research is needed to identify other factors that may improve the predictions for muscle activities and postures.